Severe Ulcerative Colitis Flare Unmasking Factor VII Deficiency - Muna Aguon, Paul; Aasen, Tyler; Salehpour, Kaivan; Mcshane, Scott (International Journal of Medicine, 2018)
We present a 22-year-old male with severe bleeding from Ulcerative Colitis. Workup revealed anemia and elevated prothrombin time, with subsequent mixing study and clotting factor levels revealing factor VII deficiency. Bleeding disorders such as Factor VII deficiency may exacerbate the degree of hemorrhage in inflammatory bowel disease flares, making prompt recognition of underlying coagulopathies crucial.